A Multiplex RT-PCR Assay for S. aureus, L. monocytogenes, and Salmonella spp. Detection in Raw Milk with Pre-enrichment - Ding, Tian; Suo, Yuanjie; Zhang, Zhaohuan; Liu, Donghong; Ye, Xingqian; Chen, Shiguo; Zhao, Yong (Frontiers in Microbiology, 2017)
This study firstly developed a multiplex real-time PCR (RT-PCR) technique combined with a pre-enrichment step to simultaneously detect Staphylococcus aureus (S. aureus), Listeria monocytogenes (L. monocytogenes) and Salmonella spp. in raw milk and the dairy farm environment (faeces, soil, feed, water) in one reaction. Brain heart infusion (BHI) broth was selected for the enrichment step to increase the density of the target bacteria by using an incubation of four hours before multiplex RT-PCR. The results showed that the detection limit of the multiplex real-time assay was approximately 102 CFU/mL for pure cultures and artificially contaminated milk without enrichment, while 12, 14, and 10 CFU/25 mL respectively for S. aureus, L. monocytogenes, and Salmonella spp. after pre-enrichment. The newly developed multiplex RT-PCR assay was applied to 46 dairy farm environmental samples and raw milk samples covering a wide variety of sample types. The results demonstrated that the multiplex RT-PCR assay coupled with the BHI enrichment broth was suitable for the simultaneous screening of S. aureus, L. monocytogenes and Salmonella spp. in the pasture environment and in raw milk. The multiplex RT-PCR assay clearly and successfully shortened the total detection time and reduced labour compared to conventional culture-based methods for testing natural samples.